Are Endogenous Androgens Linked to Female Sexuality? A Systemic Review and Meta-analysis. (1st August 2022) - Maseroli, E; Ravelli, SA; Rastrelli, G; Cipriani, S; Vignozzi, L
ABSTRACT: Introduction: The benefits of treatment with testosterone (T) in women with loss of desire suggest that low androgens may distinguish women with sexual dysfunction (SD) from others; however, evidence on this point is lacking. Objective: To answer the question: is there an association between endogenous levels of androgens and sexual function in women? Methods: An extensive search was performed in MEDLINE, Embase and PsycInfo. Four separate meta-analyses were conducted for total T, free T, Free Androgen Index (FAI) and Dehydroepiandrosterone sulphate (DHEAS). Cohort, cross-sectional and prospective studies were included.The main outcome was the association between endogenous androgens and sexual desire. Global sexual function was considered as a secondary outcome. The effect measure was expressed as standardized mean difference (SMD). Results: The meta-analysis on total T included 34 studies involving 3268 women, mean age 36.5 years. In 11 studies, a significant association was found between sexual desire, measured by validated psychometric instruments, and total T [SMD=0.59 (0.29; 0.88), p<0.0001], with a moderate effect. The association with global sexual function (n=12 studies) was also significant [SMD=0.44 (0.21; 0.67), p<0.0001]. Overall, total T was associated with a better sexual function [SMD=0.55 (0.28; 0.82), p<0.0001], with similar results obtained when Poor quality studies were removed. No association was found between total T and sexual function in PCOS or healthy women. Age showed a negative relationship with the overall outcome. No differences were found when stratifying the studies according to menopausal status, relationship status, method for T measurement (immunoassays, radioimmunoassays or mass spectrometry) or phase of the menstrual cycle. The meta-analysis of T derivatives (free T and FAI) also showed a significant, moderate association with sexual desire. In contrast, DHEAS seems not to exert any significant influence on desire, whilst showing a positive association with global sexual function. Conclusions: There appears to be a moderate association between total T levels and sexual desire/global sexual function, which is confirmed, although weak, in studies employing LC-MS. Similar results on desire were obtained for free T and FAI. DHEAS only showed a positive association with global sexual function. More research is needed. Disclosure: No